Once‐daily USL255 as adjunctive treatment of partial‐onset seizures: Randomized phase III study. Issue 7 (5th June 2014) - Chung, Steve S.; Fakhoury, Toufic A.; Hogan, R. Edward; Nagaraddi, Venkatesh N.; Blatt, Ilan; Lawson, Balduin; Arnold, Stephan; Anders, Bob; Clark, Annie M.; Laine, Dawn; Meadows, R. Shawn; Halvorsen, Mark B.; et al.
Summary Objective To evaluate the efficacy and safety of USL255, Qudexy™ XR (topiramate) extended‐release capsules, as an adjunctive treatment for refractory partial‐onset seizures (POS) in adults taking one to three concomitant antiepileptic drugs. Methods In this global phase III study (PREVAIL; NCT01142193), 249 adults with POS were randomized 1:1 to once‐daily USL255 (200 mg/day) or placebo. The primary and key secondary efficacy endpoints were median percent reduction in weekly POS frequency and responder rate (proportion of patients with ≥50% reduction in seizure frequency). Seizure freedom was also assessed. Safety (adverse events, clinical and laboratory findings), as well as treatment effects on quality of life (QOLIE‐31‐P) and clinical global impression of change (CGI‐C), were evaluated. Results Across the entire 11‐week treatment phase, USL255 significantly reduced the median percent seizure frequency and significantly improved responder rate compared with placebo. Efficacy over placebo was observed early in treatment, in patients with highly refractory POS, and in those with the most debilitating seizure types (i.e., complex partial, partial secondarily generalized). USL255 was safe and generally well tolerated with a low incidence of neurocognitive adverse events. USL255 was associated with significant clinical improvement without adversely affecting quality of life. Significance The PREVAIL phase III clinical study demonstrated that once‐daily USL255 (200 mg/day) significantly improved seizure control and was safe and generally well tolerated with few neurocognitive side effects.